Ռուսաստանը և 1915-1916թթ. Հայոց Ցեղասպանությունը. Քաղաքական մոտեցումներ և դիրքորոշումներ - Մարուքյան, Ա. (ՀՀ ԳԱԱ հրատ.)
Политика России во время геноцтда армян в 1915-1916 гг. не была однозначна, она имела колебания и зигзаги. Это оббяснялось политической борьбой двух противостоящих течений в правительстве России: армянофильской и армянофобской. Политика России определялась в зависимости от отго какое из этих течений одерживало победу в Определенном историческом отрезке времени. The policy of Russia during the Armenian genocide in 1915-1916 was not simple; it had many oscillations and zigzags. It had mwas explained of political fighting of two tendencies in Russian goverment: proarmenian and antiarmenian. The policy of Russia was depended on victory of one these tendencies in the definite historical time.
Keywords: Modern History